ANALISIS DETERMINAN PROFITABILITAS PADA 50 LEADING COMPANIES IN MARKET CAPITALIZATION DI BEI (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This study aims to identify and analyze the determination of profitability at 50 leading companies in market capitalization on the Stock Exchange. This study uses secondary data and the populations entire company at 50 leading companies in market capitalization listed on the Indonesia Stock Exchange and the sampling technique is done by purposive sampling totaling 32 companies. The results showed size, receivable turnover and a debt to equity ratio was able to explain return on assets. Then simultaneously test showed the size, receivable turnover and a debt to equity ratio significantly influence return on assets. Partial test size does not affect the return on assets. Receivable turnover and a debt to equity ratio significantly influence the return on assets.